The Effect of Leadership Style, Work Motivation And Work Environment on Employee Performance at PT. Riztech Multi Prima Cemerlang Makassar City - Irfan; Syahrunnisa; Muchriady muchran (LP2M IAIN Palopo, 2025)
This study aims to determine the effect of Leadership Style, Work Motivation and Work Environment on Employee Performance at PT. Riztech Multi Prima Cemerlang, Makassar City. The research method used is quantitative with data collection techniques through the census method using a questionnaire with a total of 52 respondents. The data obtained were analyzed using Multiple Linear Regression Analysis to determine the relationship between these variables using the SPSS V26 application. The results of the study show that Leadership style has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. The work environment has a positive and significant effect on employee performance